SAE Technical Paper Series 2011
DOI: 10.4271/2011-01-1290
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Flow Structures in a Direct-Injection Spark-Ignition Engine Using PIV, LDV and CFD

Abstract: In-cylinder air flow structures are known to play a major role in mixture preparation and engine operating limits for DISI engines. In this paper PIV was undertaken on in-cylinder flow fields for three different planes of measurement in the intake and compression strokes of a DISI engine for a lowload engine operating condition at 1500 RPM, 0.5 bar inlet plenum pressure (World Wide Mapping Point). One of these planes was vertical, cutting through the centrally located spark plug (tumble plane); the other two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…Apart from ensemble-average flow fields, the turbulence intensity u, v, w was also obtained as the RMS of the velocity measurements at each point. LDV measurements in the same engine [54] indicated that the air-flow during late compression was quite close to isotropy. Therefore, it was decided that the Turbulent Kinetic Energy (TKE) would be approximated by using the RMS of each velocity component at each point on that plane and estimating the 3 rd velocity component as the arithmetic average of the other two; this approach is addressed further in the results section.…”
Section: Flow Characterisationmentioning
confidence: 96%
See 4 more Smart Citations
“…Apart from ensemble-average flow fields, the turbulence intensity u, v, w was also obtained as the RMS of the velocity measurements at each point. LDV measurements in the same engine [54] indicated that the air-flow during late compression was quite close to isotropy. Therefore, it was decided that the Turbulent Kinetic Energy (TKE) would be approximated by using the RMS of each velocity component at each point on that plane and estimating the 3 rd velocity component as the arithmetic average of the other two; this approach is addressed further in the results section.…”
Section: Flow Characterisationmentioning
confidence: 96%
“…Details about the engine and the test bed arrangement can be found in previous publications by the current authors, e.g. [13,20,54], hence only the most relevant features are described in this section.…”
Section: Research Enginementioning
confidence: 99%
See 3 more Smart Citations